Anger Weakens Behavioral Inhibition Selectively in Contact Athletes - Xia, Xue; Zhang, Guanghui; Wang, Xiaochun (Frontiers in Human Neuroscience, 2018)
Studies have increasingly found that the aggression level of contact athletes is higher than that of non-athletes. Given that aggression levels are associated with behavioral inhibition and that athletes show better behavioral inhibition than non-athletes, it is unclear why athletes would exhibit higher aggression levels. Emotion, especially anger, is an important factor in the generation of aggressive behavior, and anger has been shown to affect behavioral inhibition. Thus, the present study examined the influence of anger on behavioral inhibition in contact athletes. An implicit emotional Go/No-go task was used that contained 50 anger-associated words and 50 neutral words as stimuli. Participants were asked to execute a key press depending on the explicit color of word and to ignore any (implicit) emotional information associated with the word. The results showed a significant interaction in performance accuracy on the No-go trials between emotion (i.e., anger-associated words versus neutral words) and group (athlete versus non-athlete). The performance accuracy of the contact athletes on anger-associated stimuli was significantly lower than that for neutral stimuli. Delta and theta oscillations were observed during the time windows of event-related potential components N2 (200–300 ms) and P3 (300–500 ms) in both groups. A time-frequency analysis indicated a significant interaction between group and emotion for both delta and theta oscillations in these two time windows. Simple effects analyses showed that stronger delta and theta oscillations were evoked during the presentation of anger-associated stimuli compared with neutral stimuli in athletes. By contrast, no significant effect was found in the control group or between the control and athlete groups. These results indicate that time-frequency analysis can effectively distinguish conventional N2 and P3 components and that implicit anger significantly weakens behavioral inhibition in contact athletes but not in non-athletes.